SEMI-BATCH EXPERIMENTAL STUDY ON MULTIPLE CARBON DIOXIDE BUBBLES ABSORPTION IN SWEETENER SOLUTION UNDER VARYING PRESSURES (Jurnal Teknologi (Sciences & Engineering), 2024)
Increasing the absorbed carbon dioxide amount in sweetener solution is a new trend to modify soft drinks. This research investigated the optimum increase in absorbed carbon dioxide within the limits of permissible food specifications in the bubble column. Response surface methodology (RSM) utilizing the Box Behnken design (BBD) was used to conduct experiments operating conditions for achieving desired responses within specified ranges of pressure (2-4 bar), temperature (5-25°C), gas flow rate (0.2–0.4 L/min), and absorbent concentration (0–150 g/L). The experimentally obtained results were fitted to a second-order polynomial model—the increase in pressure and gas flow rate results in an increase in absorption yield (YCO2). Also, increasing the gas flow rate and temperature will increase the volumetric mass transfer coefficient (KLa), while, at high pressure and pore size KLa will be reduced. According to the obtained results at optimum conditions, 4 bar, 5°C, gas flow rate 0.4 L/min, sucrose concentration of 0 g/L, and pore diffuser 0.5 μm; The CO2 content (YCO2) was 8.34 g/L. The optimum conditions for combining the effect of high CO2 content (6.125 g/L) and best KLa value (0.1043 L/min) were: 2.83 bar, 5 °C, a gas flow rate of 0.4 L/min, a sucrose concentration of 65.15 g/L, and pore diffuser of 0.5 μm.